Os desafios estratégicos da internacionalização de mulheres pesquisadoras no contexto brasileiro - Boarin, Paula Vitória Galesi Abdala (2020)
This work deals with the internationalization process of women in academia (Higher Education) as an object of study. The importance of this theme was noted when the numbers that reflect the participation of women in the most diverse professional aspects were observed. Starting the analysis in a general and broad way, it is noticed that in the academy women have a strong representation in the initial levels of the career, however, as the progress in the hierarchical level and of scientific importance there is a significant decrease in the participation of women. Having access to indicators and previous studies was an important part of determining the central objective of this research: what are the motivators, barriers and facilitators for the internationalization of the Brazilian researcher in the Brazilian context. To achieve the proposed objective, the method chosen was the qualitative one based on content analysis. Fifteen interviews were conducted with a semi-structured script. Researchers who mostly work in higher education institutions in Brazil were chosen, chosen for experiencing the phenomenon of internationalization in their careers and, thus, being able to contribute with their experiences for the construction of fundamental insights about the phenomenon. As a result of this study, it is noted that the reconciliation of multiple roles and the resistance suffered by the researchers due to stereotypes related to the profession are among the main barriers to the internationalization of their careers. The main motivators are the expectation of professional growth, personal development and benefits for third parties, such as students, the institution in which they operate and society in general. The main facilitators highlighted by the researchers are related to the institution in which they work, as policies and structures that contribute to the development of their multiple roles and the individuals around them, as career mentors with a view to internationalization. This study presents three main contributions. The first refers to the theme, increasing the depth of data through the interviewees' reports and bringing, from the perspectives of Brazilian researchers, insights into the context of Brazil. The second contribution is aimed at educational institutions, through the presentation of a scenario of current data that makes it possible to understand the networks that hinder the better use of women in academia. Finally, a contribution is presented to women researchers, so that they can act more consciously in their field, and with clear access to the possible barriers faced, also knowing those factors that can facilitate their academic career in an international scenario.